2000
DOI: 10.1002/(sici)1097-4652(200007)184:1<80::aid-jcp8>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

p21cip1 mRNA is controlled by endogenous transforming growth factor-?1 in quiescent human hematopoietic stem/progenitor cells

Abstract: Transforming growth factor-beta1 (TGF-beta1) has been described as an efficient growth inhibitor that maintains the CD34(+) hematopoietic progenitor cells in quiescence. The concept of high proliferative potential-quiescent cells or HPP-Q cells has been introduced as a working model to study the effect of TGF-beta1 in maintaining the reversible quiescence of the more primitive hematopoietic stem cell compartment. HPP-Q cells are primitive quiescent stem/progenitor cells on which TGF-beta1 has downmodulated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 46 publications
(33 reference statements)
5
31
0
Order By: Relevance
“…29 Thus, the use of antisense oligonucleotides has revealed that hHSC quiescence is mediated in part through an autocrine loop involving TGFb1. [30][31][32][33] Similar results have been obtained using either antibodies against TGF-b 25,31,34 or antibodies against the TGF-b cell-surface type II receptor (anti-TbR-II). 35 The aim of the present study was to address the question of a possible involvement of type I interferons (IFN), as negative regulators of the cell cycle of human bone marrow-derived mesenchymal precursor cells, as IFNa has been described as a potent inhibitor of marrow stromal cells.…”
Section: Introductionmentioning
confidence: 71%
“…29 Thus, the use of antisense oligonucleotides has revealed that hHSC quiescence is mediated in part through an autocrine loop involving TGFb1. [30][31][32][33] Similar results have been obtained using either antibodies against TGF-b 25,31,34 or antibodies against the TGF-b cell-surface type II receptor (anti-TbR-II). 35 The aim of the present study was to address the question of a possible involvement of type I interferons (IFN), as negative regulators of the cell cycle of human bone marrow-derived mesenchymal precursor cells, as IFNa has been described as a potent inhibitor of marrow stromal cells.…”
Section: Introductionmentioning
confidence: 71%
“…In CD34+lin7 cells, TGF ± b1 is antiproliferative (Dao et al, 1998;Fortunel et al, 2000a,b) and anti-TGF-b1 antibody has been shown to increase the recruitment of cells into cycle. TGF-b1 has been shown to increase p21 transcription in CD34+ cells (Ducos et al, 2000) and in nonhematopoietic cells (Datto et al, 1995). However, neutralization of TGF-b1 alone has not been su cient to promote cycling of CD34+ cells selected with 4-HC or 5-FU for cytokine resistance (Steinman, unpublished observations, and Dao et al, (1998)).…”
Section: P21waf1 and Hsc'smentioning
confidence: 99%
“…Treatment with TGFb1 blocking antibodies or TGFb1 antisense oligonucleotides releases the stem cells from their quiescent state to an active cycling state allowing subsequent expansion of this population to occur. 251 The differentiation of myeloid progenitors into granulocyte or monocytes, on the other hand, is enhanced by TGFb. [252][253][254] Several studies have demonstrated that the negative regulation of hematopoiesis by TGFb is mediated by the Smad proteins.…”
Section: Pi3k-akt Pathwaymentioning
confidence: 99%